Interior library GIS - Coyle, Andrew (Library hi tech, 2011)
Purpose - Geographic information systems (GIS) are used in business and government and have potentially powerful applications to the library, specifically "interior GIS" mapping of the collection itself. This paper seeks to argue for the implementation of GIS software in library collection analysis.Design methodology approach - The paper explains GIS history, the technology, design with spreadsheet and ILS database, statistical advancements, power of the GIS connection, and the importance of "democratizing" technology for libraries.Findings - GIS is a powerful tool for any business or organization that keeps inventory and monitors transactional usage. GIS is going to be implemented in libraries sooner rather than later. The libraries that implement GIS early will have an intellectual advantage over those coming on-board late. GIS should be part of collection librarian technology.Practical implications - Librarians can benefit from visually analyzing the collection and its use trends. GIS will allow librarians to forecast demand for future allocations, uncover collection strengths and weaknesses, and monitor statistics in a way that is impossible with current spreadsheets. Managers will be able to track interlibrary loan trends, branch and neighborhood use volumes and will be able to match use maps with building layout and design for better functionality and loss prevention.Social implications - GIS will revolutionize statistical analysis in every field it enters. It is argued in the paper to be the first modern tool for the twenty-first century librarian, the first piece of technology to serve the librarian first, with system and user as beneficiary of the product of GIS analysis.Originality value - This paper introduces GIS to a new audience and to those familiar with GIS, applies GIS in a new direction, to the interior space of the library and its items as subject.